High levels, partitioning and fish consumption based water guidelines of perfluoroalkyl acids downstream of a former firefighting training facility in Canada. (September 2016) - Bhavsar, Satyendra P.; Fowler, Craig; Day, Sarah; Petro, Steve; Gandhi, Nilima; Gewurtz, Sarah B.; Hao, Chunyan; Zhao, Xiaoming; Drouillard, Ken G.; Morse, Dave
Abstract: High levels of perfluoroalkyl acids (PFAAs), especially perfluorooctane sulfonic acid (PFOS), have been observed at locations in/around/downstream of the sites where PFOS-based firefighting foam was used repeatedly for a prolonged period. In this study, we conducted a detailed investigation of PFAA contamination in the Lake Niapenco area in Ontario, Canada, where among the highest ever reported levels of PFOS were recently measured in amphipods, fish and snapping turtle plasma. Levels and distribution of PFAAs in water, sediment and fish samples collected from the area varied widely. An upstream pond beside a former firefighting training area (FFTA) was confirmed as the source of PFAAs even 20 years after the last use of the foam at the FFTA. Recent PFOS concentration in water ( 60 ng/L) at Lake Niapenco, about 14 km downstream of the pond, was still 3–7 × higher than the background levels. For PFOS, Log KD ranged 1.3–2.5 (mean ± SE: 1.7 ± 0.1), Log BAFs ranged 2.4–4.7 (3.4 ± 0.05), and Log BSAFs ranged 0.7–2.9 (1.7 ± 0.05). Some fish specie s -specific differences in BAF and BSAF were observed. At Log BAF of 4.7, fish PFOS levels at Lake Niapenco could reach 15, 000 ng/g, 100 × greater than a "do not eat" advisory benchmark, without exceeding the current drinking water guideline of 300 ng/L. A fish consumption based water guideline was estimated at 1–15 ng/L, which is likely applicable worldwide given that the Log BAFs observed in this study were comparable to those previously reported in the literature. It appears that PFAA in the downstream waters increased between 2011 and 2015; however, further monitoring is required to confirm this trend. Highlights: Conducted detailed investigation of PFAA in the Lake Niapenco area, Ontario, Canada FFTA was confirmed as the source of PFAAs even 20 years after the last use of AFFF. Recent d/s PFOS (60 ng/L) still 3–7 × higher than background, and may be increasing. A fish consumption based water guideline for PFOS was estimated at 1–15 ng/L. A clean-up of the contaminated pond is advisable to prevent off-site PFAA migration. Graphical abstract: